Perfluorononanoic Acid (PFNA) Exacerbates Atopic Dermatitis by Inducing Inflammation in Mice - Jiali Xiao; Junchao Wang; Nuo Xu; Xulong Huang; Farid Khalilov; Xianfeng Huang; Xiangyong Zheng; Xiashun Xu; Shisheng Lin; Wengang Zhao; Elchin Khalilov (Toxics)
Perfluorononanoic acid (PFNA) is a ubiquitous persistent environmental pollutant, and several studies have found significant links between atopic dermatitis (AD) and prenatal exposure to PFNA. However, the relationship between PFNA and AD remains unclear. In this study, 2,4-dinitrochlorobenzene (DNCB)-treated female BALB/c mice were used as AD models to investigate the effects of PFNA and its potential mechanisms. These mice were topically applied with 5 mg/kg PFNA per day for 15 days. The results demonstrated that PFNA significantly increased AD lesion severity and clinical symptoms, including dermatitis score, ear thickness, and epidermal thickness. In addition, PFNA also increased the serum IgE level, splenic atrophy, and upregulated the expression of TNF-α, IL-6, and IL-1β, genes that are associated with skin inflammatory factors. In addition, Western blot results showed that PFNA treatment upregulated the expression of p-JNK protein. Additionally, cellular experiments indicated that RAW264.7 macrophages and mouse brain microvascular endothelial (bEnd.3) cells treated with PFNA at concentrations of 0.01–100 μM for 72 h showed no changes in cell viability. However, 100 μM PFNA upregulated the mRNA expression levels of the pro-inflammatory cytokines IL-1β and IL-6, as well as the protein expression of p-JNK, in RAW264.7 cells induced with 1 mg/mL LPS for 2 h. Similarly, PFNA increased TNF-α and IL-6 mRNA expression and p-JNK protein expression in bEnd.3 cells stimulated with 20 ng/mL TNF-α for 0.5 h. Based on these findings, we can conclude that PFNA may aggravate atopic dermatitis by promoting inflammation.